2012
DOI: 10.2217/npy.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Selegiline transdermal system in major depressive disorder

Abstract: Few methods are available to explore the impact of neurocognition in schizophrenia on behaviors performed in usual contexts. The authors developed a video ethnography approach to examine the relationship between naturalistic behaviors and research constructs of neurocognition. Video ethnographers accompanied subjects through usual routines gathering continuous video data. Researchers developed codes to measure four behavioral domains observed on video. This paper describes the psychometric characteristics to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…15 In fact, a number of newer formulations of antidepressants with improved safety and tolerability profiles with different drug delivery technologies have been introduced in the current market. [16][17][18][19] The U.S. Food and Drug Administration (FDA) approved the selegiline transdermal system (STS) for the treatment of MDD in February 2006, and it has now become the first skin (transdermal) patch indicated for MDD. 16,17 In clinical trials with STS, it has been shown to be efficacious and safe in patients with MDD; there were no reports of hypertensive crisis associated with STS, and 6 of the 7 clinical trials were conducted without dietary modifications at any dose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In fact, a number of newer formulations of antidepressants with improved safety and tolerability profiles with different drug delivery technologies have been introduced in the current market. [16][17][18][19] The U.S. Food and Drug Administration (FDA) approved the selegiline transdermal system (STS) for the treatment of MDD in February 2006, and it has now become the first skin (transdermal) patch indicated for MDD. 16,17 In clinical trials with STS, it has been shown to be efficacious and safe in patients with MDD; there were no reports of hypertensive crisis associated with STS, and 6 of the 7 clinical trials were conducted without dietary modifications at any dose.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In clinical trials with STS, it has been shown to be efficacious and safe in patients with MDD; there were no reports of hypertensive crisis associated with STS, and 6 of the 7 clinical trials were conducted without dietary modifications at any dose. 18 A metaanalysis of all 5 short-term trials evaluating treatment effects of STS for patients with MDD has been previously reported. 20 According to the results, STS demonstrated significant treatment effects on core depression symptoms (HAM-D Bech 6 items: depressed mood, guilt, work and activities, retardation, psychic anxiety, general somatic symptoms), reverse vegetative symptoms (oversleeping, overeating), motor retardation, suicide, and genital symptoms (libido).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation